Acoustic comfort requirements and classifications: Buildings vs. yachts. (1st July 2022) - Rocca, Michele; Puccio, Francesca Di; Forte, Paola; Leccese, Francesco
Abstract: Acoustic comfort is an essential need in all indoor environments where people stay for a long time. Both residential buildings and yachts must guarantee a high level of acoustics comfort. However, the international standards and guidelines framework is very fragmented. In this paper the authors propose a parallelism of the regulatory framework and scientific literature between these two sectors. In details, the most important international technical standards have been analysed in order to create a picture of acoustic requirements and acoustic classification schemes. Then a wide number of acoustic comfort indicators proposed in the scientific literature was collected and grouped. Collected data indicate that on the one hand the acoustic comfort in buildings is widely studied, but at international level a shared framework of acoustics requirements and classification schemes have not been reached. On the other hand, the acoustic comfort on board has been less investigated; the threshold values of some comfort indicators are provided in the international guidelines. In few studies, typical indicators of the building sector have been employed in yachts. The extension of the field of application of acoustic comfort indicators developed for buildings to the boat sector appears a promising solution for improving the fragmentation of the current guidelines. Highlights: Acoustic comfort requirements for building and boat sectors are compared. Regulatory framework and guidelines of both sectors are analysed. Acoustic comfort classification schemes of both sectors are analysed. In the boat sector, new acoustic quality indicators need to be used. Acoustic quality indicators used in the building sector could be useful for evaluating acoustic comfort on board.